Mineralogical study of Sand Dunes Fields in Najaf Governorate, Southern Iraq - Al-Naji, Ahmed Jawad; Al-Shammery, Thamer Abaas (Iraqi Journal of Science, 2019)
The purpose of the present paper is to define the minerals content in the Najaf Dunes fields and the origin of these sand sediments in the southwestern parts of Iraq. There are three types of dunes in this field were described, the barchan, longitudinal, and dome dunes and additional types e.g. Nabkha, Barchanoid ridges, and sand sheet dunes. The study area was divided into three areas according to the geographical position, and numerous samples were collected from this field. The mineralogical study consists from three methods these are; the first: separation of sand samples into the light and heavy minerals by heavy liquids,where performed on 30 samples. The second method; carbonate content performed on 60 samples, and the third method; X-ray diffraction performed on 20 samples. The light minerals contents composed from quartz, feldspar, and rock fragments, the rock fragments composed mainly of sedimentary, igneous, and metamorphic rock fragments. The heavy minerals are mostly composed from opaques minerals, chlorite group, garnet group, zircon, pyroxenes, amphiboles, epidotes, biotite, muscovite, tourmaline, kyanite, staurolite, rutile,and celestite. The heavy minerals analyses of all dunes, in three areas, show to the many source areas, these recent sediments and nearby older Sedimentary formations around the study areas, especially Dibidbba formation were the great influence from other geological formations. While the high percentages of carbonate content was obtained due to the presence of neighboring formations, which consists of limestone rocks (e.g. Dammam, Euphrates and Nfayil). And the present study shows a clear relation between the carbonate percentages and the grain size, as they increase with finer sizes.